2017
DOI: 10.1007/s11856-017-1562-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete homology over associative rings

Abstract: We compare two generalizations of Tate homology to the realm of associative rings: stable homology and the J-completion of Tor, also known as complete homology. For finitely generated modules, we show that the two theories agree over Artin algebras and over commutative noetherian rings that are Gorenstein, or local and complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Like stable homology, it is a generalization of Tate homology. We compare these two generalizations in [8]. From the point of view of stable homology, it is interesting to know when it agrees with complete homology, because the latter has a universal property.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like stable homology, it is a generalization of Tate homology. We compare these two generalizations in [8]. From the point of view of stable homology, it is interesting to know when it agrees with complete homology, because the latter has a universal property.…”
mentioning
confidence: 99%
“…From the point of view of stable homology, it is interesting to know when it agrees with complete homology, because the latter has a universal property. In this direction the main results in [8] are that these two homology theories agree over Iwanaga-Gorenstein rings, and for finitely generated modules over Artin algebras and complete commutative local rings. Moreover, the two theories agree with Tate homology, whenever it is defined, under the exact same condition; that is, if and only if every Gorenstein projective module is Gorenstein flat; see Theorem 6.7.…”
mentioning
confidence: 99%
“…Thus the above definitions of bounded cohomology and stable cohomology are independent of the choices of V-coresolutions. In view of Proposition 2.4, it can be proved similarly as in [16,Theorem 4.4] (see also [6,Appendix B]) that stable cohomology is actually the cohomology given in Definition 3.2.…”
Section: 1mentioning
confidence: 83%
“…Stable homology, as a broad generalization of Tate homology to the realm of associative rings, was introduced by Vogel and Goichot [9], and further studied by Celikbas, Christensen, Liang and Piepmeyer [2,3], and Emmanouil and Manousaki [6]. In their paper [2], it is shown that the vanishing of stable homology over commutative noetherian local rings can detect modules of finite projective (injective) dimension, even of finite Gorenstein dimension, which lead to some characterizations of classical rings such as Gorenstein rings, the original domain of Tate homology.…”
Section: Introductionmentioning
confidence: 99%